STRATEGI WWF TERHADAP PERLINDUNGAN HARIMAU SUMATERA DARI PERBURUAN LIAR DI INDONESIA (TAHUN 2016-2018) - Khoirunnisa Khoirunnisa; Arianti Mahendra (JURNAL POLINTER : KAJIAN POLITIK DAN HUBUNGAN INTERNASIONAL, 2021)
The Sumatran tiger population is on the edge of extinction due to uncontrolled habitat loss. The population of Sumatran tigers, which are only around 400, remaining in the forest. The main thing that causes the lack of the Sumatran tiger population is illegal hunting. Local people hunt the Sumatran tiger because people have economic problems. Thus, illegal trade emerged. Local people hunt Sumatran tigers, sell their body parts, it trusted that the body parts of tiger could heal diseases, and have magical powers for the protection and luck of the community. Thus, INGO International Organizations such as WWF and Tiger Range Countries formed the TX2 program that aims to double the tiger population. In addition, the theory used in this problem also uses Environmental Security.